Community Participation in Program Development Tourist Alleys in Makassar City - Sitti Mukhlisa Kahar Musakkir; M. Thahir Haning; Hasniati Hasniati (Borong Newinera Publisher, 2023)
This study aims to analyze community participation in the development of the tourist alley program in Makassar City, the implementation of a program requires participation from the community in developing programs implemented based on the theory of Aprellia Theresia (2014). By analyzing four participations, namely participation in decision making, participation in activities, participation in monitoring, evaluation, and participation in the utilization of results. The type of research used is descriptive qualitative research. The results of the study explained that community participation in the development of tourist alleys shows participation in decision making, explaining that the government always involves the community in decision making by sending hallway councils that have previously been appointed to represent the community in tourist alleys. Furthermore, participation in activities, research explains that the community welcomes the presence of the lorong wisata program, but there are still people who have not responded and welcomed this lorong wisata program. This is shown through the lack of public concern for the arrangement and management of hallways. Then participation in monitoring the evaluation, the community is always involved in this. The government in this case conducts evaluations and regular visits to each tourist alley to find out the aspirations and ideas needed as well as the obstacles faced by the community during the implementation of the tourist alley program.